Formulation and characterization of liposomal encapsulated systems of bioactive ingredients from traditional plant mountain germander (Teucrium montanum L.) for the incorporation into coffee drinks. (15th February 2022) - Šeremet, Danijela; Vugrinec, Kristina; Petrović, Predrag; Butorac, Ana; Kuzmić, Sunčica; Vojvodić Cebin, Aleksandra; Mandura, Ana; Lovrić, Marija; Pjanović, Rada; Komes, Draženka
Highlights: Echinacoside and verbascoside were dominant phenolics of mountain germander. High encapsulation efficiency of extracted phenolics into liposomes was achieved. Liposomes coated with biopolymers provided desirable in vitro digestion release. Abstract: Conventional and innovative (microwave-assisted and subcritical water extraction) techniques were applied to investigate the bioactive content of traditional plant – Teucrium montanum . Verbascoside and echinacoside, identified and quantified using LC-MS/MS and HPLC-PAD, were found to be the predominant phenolics in all extracts. Infusion (30 °C, 30 min) was characterized with the highest total phenolic content and antioxidant capacity and was further used for encapsulation into liposomes. Formulation of liposomes with a high encapsulation efficiency of echinacoside (68.27%) and verbascoside (80.60%), satisfactory physical properties, including size (326.2 nm) and polydispersity index (0.34), was achieved, although determined zeta potential (–23.03 mV) indicated their instability. Formulated liposomes were successfully coated with pectin and alginate that was also proved by FTIR analysis. Liposomes coated with pectin showed the most desirable in vitro digestion release of verbascoside and echinacoside, while alginate as liposome surface layer proved to be more appropriate for their retention during storage time.